On phase transitions of the Potts model with three competing interactions on Cayley tree - Akin, H.; Temir, S. (Condensed Matter Physics, 2011)
In the present paper we study a phase transition problem for the Potts model with three competing interactions, the nearest neighbors, the second neighbors and triples of neighbors and non-zero external field on Cayley tree of order two. We prove that for some parameter values of the model there is phase transition. We reduce the problem of describing by limiting Gibbs measures to the problem of solving a system of nonlinear functional equations. We extend the results obtained by Ganikhodjaev and Rozikov [Math. Phys. Anal. Geom., 2009, 12, No. 2, 141-156] on phase transition for the Ising model to the Potts model setting. У цiй статтi ми вивчаємо проблему фазового переходу для моделi Поттса з трьома конкуруючими взаємодiями, найближчих сусiдiв, наступних близьких сусiдiв i наступних за наступними близькими сусiдами,з ненульовим зовнiшнiм полем на деревi Келi другого порядку. Ми доводимо, що для деяких значень параметрiв моделi є фазовий перехiд. Ми приводимо проблему опису граничних мiр Гiббса до проблеми розв’язку системи нелiнiйних функцiональних рiвнянь. Ми розширюємо результати, отриманi Ганiходяєвим i Розiковим [Math. Phys. Anal. Geom., 2009, 12, No 2, 141–156] для фазового переходу в моделi Iзiнга,на випадок моделi Поттса.